Acquired Von Willebrand Syndrome and Blood Pump Design. Issue 12 (28th October 2018) - Rosenberg, Gerson; Siedlecki, Christopher A.; Jhun, Choon‐Sik; Weiss, William J.; Manning, Keefe; Deutsch, Steven; Pierce, William
Abstract: The existence of acquired von Willebrand syndrome (AVWS) in patients with continuous flow left ventricular assist devices (LVADs) is well documented and has been verified by numerous investigators. AVWS has not been observed to occur in pulsatile devices such as the SynCardia total artificial heart (TAH), the HeartMate XVE, and the Thoratec pulsatile ventricular assist device (PVAD) used as a single pump. AVWS can also occur in patients with aortic stenosis, ventricular septal defect, mitral stenosis, and patent ductus arteriosus. It has been experimentally verified that supraphysiologic shear stress that occurs under these conditions can cleave the von Willebrand molecule, but the critical magnitude of stress and duration is unclear. Limited experimental results demonstrate that shear stresses as low as 5 Pa (50 dyne/cm 2 ) can cause cleavage. Stresses in current centrifugal pumps can be as high as two orders of magnitude greater than this value. Pulsatile LVADs have stresses almost two orders of magnitude less than continuous flow LVADs. In order to improve continuous flow LVADs, the challenge for designers is to first determine the magnitude and duration of stress that is causing AVWS and then, if possible, design a pump below these stresses.